Makna dan Peran Ekoliterasi Dalam Pembetukan Identitas Profesional Mahasiswa Perpustakaan dan Sains Informasi - Ardiansyah, Fatri; Ilmi, Uswatul; Setya Permana, Indra (Literatify: Trends in Library Developments, 2026)
This study aims to analyze the meaning and role of ecoliteracy in shaping the professional identity of library and information science students. The approach used in this study is descriptive qualitative, with data collection conducted through observation and in-depth interviews with nine respondents from the library and information science program at Muhammadiyah University of Sinjai. Based on the data analysis, the results of this study reveal three main findings. First, students' understanding of ecoliteracy is still limited, often viewed only as practical environmental concerns and not as systemic ecological awareness. Second, the internalization of ecoliteracy values into the professional attitudes of prospective librarians is still low. This is due to the lack of integration of ecoliteracy concepts into the curriculum, the lack of role models, and the absence of adequate guidance. Third, ecoliteracy is seen as a complementary element that can enrich and modernize the image of the librarian profession, but has not yet become the core of their professional identity. This study concludes that ecoliteracy has strategic potential to shape librarian identities that are relevant to the global challenges of sustainability.